2011
DOI: 10.1155/2011/373859
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Hemoglobin-Stabilizing Protein: An Erythroid Molecular Chaperone

Abstract: Alpha-hemoglobin-stabilizing protein (AHSP) is an erythroid-specific protein that acts as a molecular chaperone for the free α chains of hemoglobin. Evidence strongly suggests that AHSP participates in hemoglobin synthesis and may act to neutralize the cytotoxic effects of excess free alpha-globin subunits that accumulate both in normal and beta-thalassemic erythroid precursor cells. As such, AHSP seems to be essential for normal erythropoiesis, and impaired upregulation of AHSP may lead to premature erythroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Prior studies indicate two potential functions for AHSP during normal and pathologic erythropoiesis (8,26,63). First, AHSP acts as a molecular chaperone to bind and stabilize nascent ␣-globin folding intermediates prior to reaction with ␤-globin and assembly into HbA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies indicate two potential functions for AHSP during normal and pathologic erythropoiesis (8,26,63). First, AHSP acts as a molecular chaperone to bind and stabilize nascent ␣-globin folding intermediates prior to reaction with ␤-globin and assembly into HbA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that loss of AHSP expression results in globin precipitation in murine model and caused ineffective erythropoiesis, and more exacerbates ß-thalassemia [31, 32] and AHSP - knockdown cells demonstrated an increased reactive oxygen species (ROS) production and increased rate of apoptosis [33]. Moreover, AHSP gene expression is controlled by some regulatory elements, such as GATA binding protein 1 (GATA-1) [30], Organic cation transporter 1 (Oct-1) [34] and Erythroid Kruppel-like factor (EKLF) [35-37].…”
Section: Discussionmentioning
confidence: 99%
“…2D, blue spheres) (reviewed in Weiss et al 2005;Favero and Costa 2011). These a-globin variants include Hbs Prato (a1 or a2 31 [B12] Arg .…”
Section: Selected Variants That Illustrate Important Aspects Of Hemogmentioning
confidence: 99%